GAMBARAN TINGKAT PENGETAHUAN TENTANG PENGGUNAAN LENSA KONTAK PADA SISWA DAN GURU DI SEKOLAH MENENGAH ATAS NEGERI 1 DAN 9 KOTA PEKANBARU - Yunia Utami; Efhandi Nukman; Miftah Azrin (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2016)
ABSTRACTContact lens is a result of technology in ophthalmology which is used as an alternative for eye glasses to correct the refractive error. The use of contact lens also has negative effect mainly for those who use it continuously without paying attention to its health impact. This research aimed to assess knowledge about the use of contact lens in students and teachers of Sekolah Menengah Atas Negeri (SMAN/State High School) 1 and SMAN 9 Pekanbaru. The research was done in both high schools room on December 2015. Population amount of this research was 353 which consisted of all class XI students and all teachers of SMAN 1 and SMAN 9 Pekanbaru. The sample taking method used was total sampling method. Primary data was taken and then managed by using computerized method. Data analysis used in this research was univariate and bivariate analysis. Result of the research showed that most of respondents (students) in SMAN 1 were female (21 persons, 52,5%), 25 persons (62,5%) of them use contact lens for fashion reason. There were 28 persons (70,0%) of respondents who had less knowledge about contact lens usage. The cooperation between school and health worker especially ophthalmologist is needed to give information and improve the knowledge of students and teachers about the correct and safe use of contact lens.Keywords : Knowledge , Contact Lenses